TYPIFICATION OF DESIGN SOLUTIONS FOR SPECIAL CLOTHING PRODUCTS - H. M. Yunuskhodjaeva (Journals Park Publishing, 2022)
As a result of systematization of existing design solutions of work clothes, combining them with characteristic features and combining them with groups of design situations, we have identified three main types of structures: structures with traditional separation and shape of parts, a high level of static and a satisfactory level of dynamic compatibility of clothing, characterized by the availability of design information
Keywords: Special clothing, ergonomic design, constructive parameter, design in design, design, environment, protection.